Non-oriented electrical steel sheet and method of manufacturing the same

KR103019206B1Active Publication Date: 2026-09-15NIPPON STEEL CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020257028526
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-02-01
Filing Date
2024-02-01
Publication Date
2026-09-15
Estimated Expiration
2044-02-01

Smart Images

  • Figure 112025097901153-PCT00001
    Figure 112025097901153-PCT00001
  • Figure 112025097901153-PCT00002
    Figure 112025097901153-PCT00002
Patent Text Reader

Abstract

The chemical composition of the base material, in mass%, is C: 0.0040% or less, Si: greater than 3.50% and less than or equal to 4.50%, Mn: less than 0.60%, Al: 0.30 to 0.90%, P: 0.030% or less, S: 0.0018% or less, N: 0.0040% or less, Ti: less than 0.0040%, Nb: less than 0.0050%, Zr: less than 0.0050%, V: less than 0.0050%, Cu: less than 0.200%, Ni: less than 0.500%, the sum of one or two of Sn and Sb is 0.005 to 0.060%, the remainder is Fe and impurities, satisfying [4.2≤Si+Al+0.5×Mn≤4.9], and the average crystal grain size of the base material is, A non-oriented electrical steel sheet having a thickness greater than 40㎛ and less than or equal to 140㎛, a {111} orientation density of 4.0 or less, and a base material sheet thickness of 0.10 to 0.30mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a non-oriented electrical steel sheet and a method for manufacturing the same. Background Technology

[0002] In recent years, global environmental issues have garnered significant attention, and the demand for energy conservation measures has been rising ever higher. Among these, there is a strong demand for higher efficiency in electrical equipment. Consequently, there is an increasing demand for improved magnetic properties in non-oriented electrical steel sheets, which are widely used as core materials for motors and generators. This trend is particularly pronounced in drive motors for electric and hybrid vehicles, as well as in compressor motors for air conditioners. Furthermore, there is a growing demand for higher output power for drive motors and compressor motors, which is effective for miniaturizing equipment.

[0003] To achieve high motor efficiency, it is crucial to reduce iron and copper losses, which are the primary sources of losses. Reducing iron loss is effective in the electrical steel sheets used as the motor core, while increasing the magnetic flux density of the electrical steel sheets is effective for reducing copper loss. Meanwhile, achieving high motor output requires high torque and high-speed rotation. Increasing the magnetic flux density of the electrical steel sheets is effective for high torque, while increasing the strength of the electrical steel sheets is effective for high-speed rotation. Therefore, to advance high motor efficiency and output, electrical steel sheets with low iron loss, high magnetic flux density, and high strength are required.

[0004] The motor core of the various motors described above is composed of a stator and a rotor. The characteristics required for the stator and rotor constituting the motor core are not the same. While excellent magnetic properties (low iron loss and high magnetic flux density) are required for the stator, low iron loss and excellent mechanical properties (high strength) are required for the rotor.

[0005] Since the characteristics required for the stator and the rotor are different, the desired characteristics can be realized by manufacturing non-oriented electrical steel sheets for the stator and non-oriented electrical steel sheets for the rotor separately. However, preparing two types of non-oriented electrical steel sheets complicates the core manufacturing process and leads to a decrease in yield. Therefore, in order to realize the low iron loss and high strength required for the rotor, as well as the low iron loss and high magnetic flux density required for the stator, non-oriented electrical steel sheets with excellent magnetic properties and also excellent strength have been considered for a long time.

[0006] For example, in patent documents 1 to 4, attempts have been made to realize excellent magnetic properties and high strength. Prior art literature

[0007] International Publication No. 2019 / 017426, International Publication No. 2020 / 091039, International Publication No. 2020 / 091043, Japanese Patent Publication No. 2010-90474 The problem to be solved

[0008] However, in order to realize non-oriented electrical steel sheets that achieve both low iron loss and high strength, as disclosed in Patent Documents 1 to 4, it is necessary to include a large amount of alloying elements, which has a problem in that toughness is reduced and fracture during cold rolling is likely to occur.

[0009] The present invention was made to solve these problems and aims to stably provide a non-oriented electrical steel sheet having excellent magnetic properties and high strength. means of solving the problem

[0010] The present invention is characterized by the following non-oriented electrical steel sheet and a method for manufacturing the same.

[0011] (1) The chemical composition of the base material is, in mass%,

[0012] C: 0.0040% or less,

[0013] Si: Exceeding 3.50% and up to 4.50%,

[0014] Mn: Less than 0.60%,

[0015] Al: 0.30 to 0.90%,

[0016] P: 0.030% or less,

[0017] S: 0.0018% or less,

[0018] N: 0.0040% or less,

[0019] Ti: Less than 0.0040%,

[0020] Nb: Less than 0.0050%,

[0021] Zr: Less than 0.0050%,

[0022] V: Less than 0.0050%,

[0023] Cu: Less than 0.200%,

[0024] Ni: Less than 0.500%,

[0025] Total of one or both of Sn and Sb: 0.005 to 0.060%,

[0026] Remainder: Fe and impurities,

[0027] Satisfy the following equation (i), and

[0028] The average crystal grain size of the above base material is greater than 40㎛ and less than or equal to 140㎛, and

[0029] The accumulation degree of the {111} orientation at a position 1 / 4 of the plate thickness from the surface of the above base material is 4.0 or less, and

[0030] The plate thickness of the above base material is 0.10 to 0.30 mm,

[0031] Non-oriented electrical steel sheet.

[0032] 4.2≤Si+Al+0.5×Mn≤4.9… (i)

[0033] However, the element symbols in the above formula represent the content (mass%) of each element.

[0034] (2) Tensile strength of 580 MPa or higher,

[0035] The non-oriented electrical steel sheet described in (1) above.

[0036] (3) having an insulating film on the surface of the above base material,

[0037] Non-oriented electrical steel sheet described in (1) or (2) above.

[0038] (4) A method for manufacturing non-oriented electrical steel sheets as described in any of (1) to (3) above, and

[0039] In mass %,

[0040] C: 0.0040% or less,

[0041] Si: Exceeding 3.50% and up to 4.50%,

[0042] Mn: Less than 0.60%,

[0043] Al: 0.30 to 0.90%,

[0044] P: 0.030% or less,

[0045] S: 0.0018% or less,

[0046] N: 0.0040% or less,

[0047] Ti: Less than 0.0040%,

[0048] Nb: Less than 0.0050%,

[0049] Zr: Less than 0.0050%,

[0050] V: Less than 0.0050%,

[0051] Cu: Less than 0.200%,

[0052] Ni: Less than 0.500%,

[0053] Total of one or both of Sn and Sb: 0.005 to 0.060%,

[0054] Remainder: Fe and impurities,

[0055] For a steel ingot having a chemical composition satisfying the following equation (i),

[0056] A hot rolling process, a hot-rolled plate annealing process in which the cracking temperature is 800 to 920°C and the cracking time is 1 second to 10 minutes, a descaling process in which pickling is performed after shot blasting, a cold rolling process in which the plate thickness is reduced to 0.10 to 0.30 mm, and a finishing annealing process in which the plate is heated to a temperature of 850°C or higher such that the heating rate in the temperature range of 500 to 850°C is 400°C / s or higher, and the cracking temperature is 900 to 1050°C and the cracking time is 1 second to 10 minutes are performed in sequence.

[0057] Method for manufacturing non-oriented electrical steel sheets.

[0058] 4.2≤Si+Al+0.5×Mn≤4.9… (i)

[0059] However, the element symbols in the above formula represent the content (mass%) of each element. Effects of the invention

[0060] According to the present invention, a non-oriented electrical steel sheet having excellent magnetic properties and high strength can be reliably obtained. Specific details for implementing the invention

[0061] In order to solve the above problem, the inventors conducted a thorough examination and arrived at the following findings.

[0062] To obtain high-strength, low-iron loss and high-magnetic flux density non-oriented electrical steel sheets while ensuring toughness during cold rolling, it is necessary to optimize the content of key alloying elements such as Si, Mn, and Al.

[0063] Specifically, Si, which has the highest solid solution strengthening ability and contributes most to the increase in electrical resistance, is contained in an amount of more than 3.50% and less than or equal to 4.50%. In addition, Al is contained in an amount of 0.30% or more to improve grain growth and to obtain stable, excellent magnetic properties. Meanwhile, to suppress the deterioration of toughness, the Al content is kept at 0.90% or less.

[0064] In addition, Mn is an element that contributes to the increase in electrical resistance, as it has the lowest solid solution strengthening ability among the three elements but exhibits minimal toughness degradation. However, as a result of repeated investigations by the inventors, it was found that if Mn, which has a lower solid solution strengthening ability compared to Si and Al, is contained in excess, the decrease in magnetic flux density is significant relative to the increase in strength, and it becomes difficult to stably improve magnetic properties when the Mn content is high. Therefore, the Mn content is kept below 0.60%.

[0065] In the manufacturing process of non-oriented electrical steel sheets, it is common practice to perform hot-rolled sheet annealing prior to cold rolling. However, when the steel sheet has a high Si content and it is necessary to reduce the sheet thickness to minimize iron loss, it is desirable to lower the cracking temperature during hot-rolled sheet annealing to suppress troubles such as sheet fracture and corner cracking during cold rolling. On the other hand, it is known that magnetic flux density increases as the cracking temperature during hot-rolled sheet annealing increases, and lowering the cracking temperature results in a decrease in magnetic flux density.

[0066] Therefore, the inventors investigated a method to improve magnetic flux density while lowering the cracking temperature during hot-rolled sheet annealing. As a result, they discovered that by performing rapid heating during the finishing annealing after cold rolling, it is possible to suppress the development of textures unfavorable to magnetic properties, thereby enabling the suppression of the decrease in magnetic flux density even when the cracking temperature during hot-rolled sheet annealing is low.

[0067] In addition, as a result of the inventors conducting experiments to rapidly heat up to various attainable temperatures, it was found that even if rapid heating was performed, the effect of improving magnetic properties was not confirmed when the attainable temperature was low, and that magnetic properties were improved by rapidly heating to a temperature of 850°C or higher.

[0068] The present invention is based on the above findings. Below, each requirement of the present invention will be explained in detail.

[0069] 1. Overall Structure

[0070] The non-oriented electrical steel sheet according to one embodiment of the present invention is suitable for both stator and rotor because it has excellent magnetic properties and also high strength. In addition, the non-oriented electrical steel sheet according to the present embodiment preferably has an insulating film on the surface of the base material described below.

[0071] 2. Chemical composition of the base material

[0072] The reason for limiting each element is as follows. Additionally, in the following description, "%" regarding content means "mass%".

[0073] C: 0.0040% or less

[0074] Carbon (C) is an element that causes iron loss deterioration in non-oriented electrical steel sheets. If the C content exceeds 0.0040%, the iron loss of the non-oriented electrical steel sheet deteriorates, and good magnetic properties cannot be obtained. Therefore, the C content is set to 0.0040% or less. It is preferable that the C content be 0.0035% or less, and more preferable that it be 0.0030% or less. In addition, since C contributes to the high strength of non-oriented electrical steel sheets, if one wishes to obtain this effect, it is preferable that the C content be 0.0005% or more, and more preferable that it be 0.0010% or more.

[0075] Si: Over 3.50% and under 4.50%

[0076] Silicon (Si) is an element that increases the electrical resistance of steel, thereby reducing eddy current losses and improving iron loss in non-oriented electrical steel sheets. Additionally, because Si has a high solid solution strengthening ability, it is an effective element for increasing the strength of non-oriented electrical steel sheets. To obtain these effects, the Si content is set to exceed 3.50%. It is preferable for the Si content to be 3.60% or higher, more preferable for 3.70% or higher, and even more preferable for 3.80% or higher. On the other hand, if the Si content is excessive, workability deteriorates significantly, making it difficult to perform cold rolling. Therefore, the Si content is set to 4.50% or less. It is preferable for the Si content to be 4.40% or less, and more preferable for 4.30% or less.

[0077] Mn: Less than 0.60%

[0078] Manganese (Mn) is an effective element for increasing the electrical resistance of steel, reducing eddy current losses, and improving iron loss in non-oriented electrical steel sheets. However, since Mn has lower solid solution strengthening ability compared to Si and Al, a large amount is required to obtain high strength, which leads to a significant decrease in magnetic flux density. Therefore, the Mn content should be less than 0.60%. It is preferable that the Mn content be 0.55% or less, and more preferable that it be 0.50% or less. Although it is not necessary to set a lower limit for the Mn content, if the above effects are desired, it is preferable that the Mn content be 0.10% or more, and more preferable that it be 0.20% or more.

[0079] Al: 0.30 to 0.90%

[0080] Aluminum (Al) is an element that reduces eddy current losses by increasing the electrical resistance of steel and improves iron loss in non-oriented electrical steel sheets. Additionally, although not to the same extent as Si, Al is an element that contributes to the high strength of non-oriented electrical steel sheets through solid solution strengthening. Furthermore, the addition of an appropriate amount of Al suppresses the refinement of AlN generated by combining with N in the steel and improves grain growth during finish annealing. To obtain these effects, the Al content should be 0.30% or more. It is preferable for the Al content to be 0.40% or more, more preferable for it to exceed 0.45%, and even more preferable for it to be 0.50% or more. On the other hand, if the Al content is excessive, toughness deteriorates, increasing the risk of fracture during cold rolling. Therefore, the Al content should be 0.90% or less. It is preferable for the Al content to be 0.80% or less, and more preferable for it to be 0.70% or less.

[0081] In this embodiment, the electrical resistance of the steel is secured by appropriately controlling the content of Si, Al, and Mn. In addition, it is necessary to appropriately control the content of Si, Al, and Mn from the perspective of securing strength. Meanwhile, an upper limit is also required from the perspective of securing magnetic flux density and toughness. Therefore, in addition to the content of Si, Al, and Mn being within the above ranges, it is necessary to satisfy the following equation (i). The value of the middle side of the following equation (i) is preferably 4.3 or higher, more preferably 4.4 or higher, preferably 4.8 or lower, and more preferably 4.7 or lower.

[0082] 4.2≤Si+Al+0.5×Mn≤4.9… (i)

[0083] However, the element symbols in the above formula represent the content (mass%) of each element.

[0084] P: 0.030% or less

[0085] Phosphorus is contained in steel as an impurity, and if its content is excessive, the toughness of non-oriented electrical steel sheets is significantly reduced. Therefore, the P content is set to 0.030% or less. It is preferable that the P content be 0.025% or less, and more preferable that it be 0.020% or less. In addition, since an extreme reduction in the P content may cause an increase in manufacturing costs, it is preferable that the P content be 0.003% or more, and more preferable that it be 0.005% or more.

[0086] S: 0.0018% or less

[0087] Sulfur (S) is an element that degrades the magnetic properties of non-oriented electrical steel sheets by increasing iron loss through the formation of fine precipitates of MnS. Therefore, the S content is to be 0.0018% or less. It is preferable that the S content be 0.0016% or less, and more preferable that it be 0.0014% or less. Furthermore, since an extreme reduction in the S content may lead to an increase in manufacturing costs, it is preferable that the S content be 0.0001% or more, more preferable that it be 0.0003% or more, and even more preferable that it be 0.0005% or more.

[0088] N: 0.0040% or less

[0089] Nitrogen (N) is an element that is inevitably incorporated into steel and forms nitrides, which increase iron loss and degrade the magnetic properties of non-oriented electrical steel sheets. Therefore, the N content should be 0.0040% or less. It is preferable that the N content be 0.0030% or less, and more preferable that it be 0.0020% or less. In addition, since an extreme reduction in N content may lead to an increase in manufacturing costs, it is preferable that the N content be 0.0005% or more.

[0090] Ti: Less than 0.0040%

[0091] Titanium (Ti) is an element that is inevitably incorporated into steel and can combine with carbon or nitrogen to form precipitates (carbides, nitrides). When carbides or nitrides are formed, these precipitates themselves degrade the magnetic properties of the non-oriented electrical steel sheet. Furthermore, they inhibit grain growth during finish annealing, thereby degrading the magnetic properties of the non-oriented electrical steel sheet. Therefore, the Ti content should be less than 0.0040%. It is preferable that the Ti content be 0.0030% or less, and more preferable that it be 0.0025% or less. Additionally, since an extreme reduction in Ti content may lead to an increase in manufacturing costs, it is preferable that the Ti content be 0.0005% or more.

[0092] Nb: Less than 0.0050%

[0093] Niobium (Nb) is an element that contributes to high strength by combining with carbon or nitrogen to form precipitates (carbides, nitrides), but these precipitates themselves degrade the magnetic properties of non-oriented electrical steel sheets. Therefore, the Nb content should be less than 0.0050%. It is preferable that the Nb content be 0.0040% or less, more preferable that it be 0.0030% or less, and even more preferable that it be 0.0020% or less. Furthermore, since an extreme reduction in Nb content may lead to an increase in manufacturing costs, it is preferable that the Nb content be 0.0001% or more.

[0094] Zr: Less than 0.0050%

[0095] Zr (zirconium) is an element that contributes to high strength by combining with carbon or nitrogen to form precipitates (carbides, nitrides), but these precipitates themselves degrade the magnetic properties of non-oriented electrical steel sheets. Therefore, the Zr content should be less than 0.0050%. It is preferable that the Zr content be 0.0040% or less, more preferable that it be 0.0030% or less, and even more preferable that it be 0.0020% or less. In addition, since an extreme reduction in Zr content may lead to an increase in manufacturing costs, it is preferable that the Zr content be 0.0001% or more.

[0096] V: Less than 0.0050%

[0097] Vanadium (V) is an element that contributes to high strength by combining with carbon or nitrogen to form precipitates (carbides, nitrides), but these precipitates themselves degrade the magnetic properties of non-oriented electrical steel sheets. Therefore, the V content should be less than 0.0050%. It is preferable that the V content be 0.0040% or less, more preferable that it be 0.0030% or less, and even more preferable that it be 0.0020% or less. In addition, since an extreme reduction in V content may lead to an increase in manufacturing costs, it is preferable that the V content be 0.0001% or more.

[0098] Cu: Less than 0.200%

[0099] Copper (Cu) is an element that is inevitably incorporated into steel. Intentionally including Cu increases the manufacturing cost of non-oriented electrical steel sheets. Therefore, in this embodiment, there is no need to actively include Cu, and it is sufficient to have it at an impurity level. The Cu content is set to less than 0.200%, which is the maximum value that can be inevitably incorporated during the manufacturing process. It is preferable that the Cu content be 0.150% or less, and more preferable that it be 0.100% or less. Furthermore, while the lower limit of the Cu content is not particularly limited, an extreme reduction in the Cu content may lead to an increase in manufacturing costs. Therefore, it is preferable that the Cu content be 0.001% or more, more preferable that it be 0.003% or more, and even more preferable that it be 0.005% or more.

[0100] Ni: Less than 0.500%

[0101] Nickel (Ni) is an element that is inevitably incorporated into steel. However, since Ni is also an element that improves the strength of non-oriented electrical steel sheets, it may be intentionally included. However, because Ni is expensive, the Ni content should be less than 0.500%. It is preferable that the Ni content be 0.400% or less, and more preferable that it be 0.300% or less. Furthermore, while there is no specific lower limit for the Ni content, an extreme reduction in Ni content may lead to an increase in manufacturing costs. Therefore, it is preferable that the Ni content be 0.001% or more, more preferable that it be 0.003% or more, and even more preferable that it be 0.005% or more. Additionally, when intentionally included, it is preferable that the Ni content be 0.200% or more.

[0102] Total of one or both of Sn and Sb: 0.005 to 0.060%

[0103] Sn (tin) and Sb (antimony) have the effect of improving the texture and increasing the magnetic flux density of non-oriented electrical steel sheets. Furthermore, by segregating on the surface of the base material and suppressing oxidation and nitridation during annealing, they are also useful elements for securing low iron loss in non-oriented electrical steel sheets. To obtain these effects, the total content of one or two of Sn and Sb is set to 0.005% or more. It is preferable that the total content be 0.010% or more, and more preferable that it be 0.015% or more. On the other hand, if the total content of Sn and Sb is excessive, the toughness of the steel decreases, making cold rolling difficult. Therefore, the total content of one or two of Sn and Sb is set to 0.060% or less. It is preferable that the total content be 0.050% or less, and more preferable that it be 0.040% or less.

[0104] In the chemical composition of the base material of the non-oriented electrical steel sheet of the present invention, the remainder is Fe and impurities. Here, "impurities" refers to components that are incorporated due to various factors of the manufacturing process, such as raw materials like ore and scrap, when steel is manufactured industrially, and are permitted within a range that does not adversely affect the present invention.

[0105] In addition, regarding the content of Cr and Mo as impurity elements, there is no specific specification. In the non-oriented electrical steel sheet according to the present embodiment, even if these elements are contained in a range of 0.5% or less each, there is no particular effect on the properties of the non-oriented electrical steel sheet according to the present embodiment. In addition, even if Ca and Mg are contained in a range of 0.002% or less each, there is no particular effect on the properties of the non-oriented electrical steel sheet according to the present embodiment. Even if rare earth elements (REM) are contained in a range of 0.004% or less, there is no particular effect on the properties of the non-oriented electrical steel sheet according to the present embodiment. In addition, in the present embodiment, REM refers to a total of 17 elements consisting of Sc, Y, and lanthanides, and the content of REM refers to the total content of these elements.

[0106] O is also an impurity element, but even if it is contained in a range of 0.035% or less, it does not affect the properties of the non-oriented electrical steel sheet according to the present embodiment. Since O may be incorporated into the steel during the annealing process, even if it is contained in a range of 0.010% or less at the slab stage (i.e., ladle value), it does not particularly affect the properties of the non-oriented electrical steel sheet according to the present embodiment.

[0107] In addition, in addition to the above elements, elements such as Zn, Pb, Bi, As, B, and Se may be included as impurity elements, but if the content of each is in the range of 0.0050% or less, it does not impair the properties of the non-oriented electrical steel sheet according to the present embodiment.

[0108] The chemical composition of the base material of the non-oriented electrical steel sheet according to the present embodiment can be determined using various known measurement methods. For example, it may be measured using ICP emission analysis, gravimetric analysis, or spark discharge emission analysis. Additionally, C and S may be measured using the combustion-infrared absorption method, N may be measured using the inert gas combustion-thermal conductivity method, and O may be measured using the inert gas melting-non-dispersive infrared absorption method.

[0109] 3. Crystal grain size

[0110] In this embodiment, the average crystal grain size of the base material is set to be greater than 40 μm and less than or equal to 140 μm. By making the average crystal grain size of the base material greater than 40 μm, it is possible to suppress the deterioration of hysteresis loss and improve magnetic properties. On the other hand, by making the average crystal grain size 140 μm or less, an effect of improving steel strength is obtained, and iron loss deterioration caused by an increase in eddy current loss can be suppressed. The average crystal grain size is preferably 50 μm or more, and more preferably 60 μm or more. In addition, the average crystal grain size is preferably 130 μm or less, and more preferably 120 μm or less.

[0111] In addition, in the present invention, the average crystal grain size of the base material is determined according to JIS G 0551: 2013 “Method for microscopic examination of steel-grain size”.

[0112] 4. Collective Organization

[0113] In this embodiment, the development of a texture that degrades magnetic properties is suppressed. Specifically, the density of {111} orientations is set to 4.0 or less. By suppressing the development of {111} orientations, it becomes possible to improve magnetic properties. It is preferable that the density of {111} orientations be 3.8 or less, and more preferable that it be 3.6 or less. Although it is not necessary to provide a lower limit for the density of {111} orientations, 1.0 serves as a practical lower limit.

[0114] The degree of accumulation of the {111} orientation is measured by an X-ray diffraction device. Furthermore, the degree of accumulation is a numerical value obtained by measuring the X-ray intensity of a standard sample and a test material that do not have accumulation in a specific orientation under the same conditions using the X-ray diffraction method, and dividing the obtained X-ray intensity of the test material by the X-ray intensity of the standard sample. The specific measurement method is as follows. The measurement was performed on the polished surface of the base material of the non-oriented electrical steel sheet of the test material, after removing it from one side surface to a depth of 1 / 4 of the sheet thickness by chemical polishing. The degree of accumulation of the {111} orientation is obtained from the Orientation Distribution Functions (ODF), which represent the three-dimensional texture calculated by the series expansion method based on the pole figures of the {200}, {110}, {310}, and {211} planes on α-Fe measured by the X-ray diffraction device. The average value of the integration density from φ1=0 to 90° at Φ=55° of the φ2=45° cross-section of the ODF marking was defined as the integration density of the {111} orientation. The integration density from φ1=0 to 90° was measured at a 5° pitch, and the average value of 19 integration densities from 0° to 90° was used.

[0115] Also, the {111} direction is also {111} <011> Direction and {111} <112> There are cases where it is classified by direction, etc. However, {111} <011> The orientation density is the numerical value of the density of φ1=0° at Φ=55° on the φ2=45° cross-section of the ODF indication, and {111} <112> The degree of orientation concentration is a numerical value of the degree of orientation concentration from Φ=55° to φ1=30° in the φ2=45° cross-section of the ODF display. Therefore, it is measured by a different method from the degree of orientation concentration of {111}, which is represented as the average value of the degree of orientation from Φ=55° to φ1=0 to 90° in the φ2=45° cross-section of the ODF display of the present invention.

[0116] 5. Personal characteristics

[0117] In the non-oriented electrical steel sheet according to the present embodiment, the fact that the magnetic properties are excellent means that the iron loss W 10 / 400 This is low, and magnetic flux density B 50 This means high.

[0118] Here, self-characteristics (iron hand W 10 / 400 and magnetic flux density B 50 ) shall be measured in accordance with the Epstein test method specified in JIS C 2550-1: 2011. In addition, at this time, the density of the steel plate is 7.65 g / cm³ 3 As such, self-measurement is performed. In addition, iron loss W 10 / 400 represents the iron loss occurring under the condition that the maximum magnetic flux density is 1.0T and the frequency is 400Hz, and the magnetic flux density B 50 represents the magnetic flux density in a magnetic field of 5000 A / m.

[0119] In the non-oriented electrical steel sheet according to the present embodiment, iron loss W 10 / 400 "This low" means that it is 14.5 W / kg or less for a plate thickness of 0.26 mm or more, 12.5 W / kg or less for a plate thickness of 0.21 to 0.25 mm, and 11.2 W / kg or less for a plate thickness of 0.20 mm or less. In addition, magnetic flux density B 50 This means that if the plate thickness is 0.26 mm or more, it is 1.64 T or more; if the plate thickness is 0.21 to 0.25 mm, it is 1.63 T or more; and if the plate thickness is 0.20 mm or less, it is 1.62 T or more.

[0120] 6. Mechanical properties

[0121] The non-oriented electrical steel sheet according to the present embodiment has high strength. Although there is no need to specifically limit the tensile strength, it is preferable that the tensile strength be 580 MPa or higher. It is more preferable that the tensile strength be 590 MPa or higher, and even more preferable that it be 600 MPa or higher. Here, the tensile strength is measured by performing a tensile test in accordance with JIS Z 2241: 2011.

[0122] 7. Plate thickness

[0123] In the non-oriented electrical steel sheet according to the present embodiment, the thickness of the base material is 0.10 mm or more from the perspective of manufacturing costs for cold rolling and finish annealing. On the other hand, from the perspective of reducing iron loss, the thickness of the base material is 0.30 mm or less. Accordingly, the thickness of the base material of the non-oriented electrical steel sheet according to the present embodiment is 0.10 to 0.30 mm. The thickness of the base material is preferably 0.15 to 0.27 mm.

[0124] 8. Insulating film

[0125] In the non-oriented electrical steel sheet according to the present embodiment, it is preferable to have an insulating film on the surface of the base material. Since the non-oriented electrical steel sheet is used after being laminated following the punching of a core blank, by providing an insulating film on the surface of the base material, eddy currents between sheets can be reduced, and it becomes possible to reduce eddy current losses as a core.

[0126] The type of insulating film is not particularly limited, and it is possible to use known insulating films used as insulating films for non-oriented electrical steel sheets. As such an insulating film, for example, a composite insulating film that is mainly composed of inorganic materials and further includes organic materials can be cited. Here, a composite insulating film is an insulating film in which fine organic resin particles are dispersed, mainly composed of at least one of inorganic materials such as, for example, metal chromate salts, metal phosphate salts, or colloidal silica, Zr compounds, or Ti compounds. In particular, from the perspective of reducing the environmental burden during manufacturing, which has been a growing demand in recent years, an insulating film using metal phosphate salts, Zr or Ti coupling agents, or their carbonates or ammonium salts as starting materials is preferably used.

[0127] The amount of insulating film applied is not particularly limited, but, for example, 200 to 3,000 mg / m² per side 2 It is desirable to set it to approximately 300 to 2,500 mg / m² per side. 2 It is more desirable to do so. By forming an insulating film such that the amount of adhesion falls within the above range, it becomes possible to maintain excellent uniformity. In addition, when measuring the amount of adhesion of the insulating film retrospectively, various known measurement methods can be used; for example, a method of measuring the mass difference before and after immersion in a sodium hydroxide aqueous solution or a fluorescent X-ray method using a calibration curve method can be appropriately used.

[0128] 9. Manufacturing method

[0129] The non-oriented electrical steel sheet according to the present embodiment is not particularly limited in terms of the manufacturing method, but it can be manufactured by sequentially performing a hot rolling process, a hot-rolled sheet annealing process, a descaling process, a cold rolling process, and a finishing annealing process on a steel ingot having the chemical composition described above, for example, under the conditions shown below. In addition, when an insulating film is formed on the surface of the base material, the insulating film formation process is performed after the finishing annealing process. Each process will be described in detail below.

[0130] Hot Rolling Process

[0131] A steel ingot (slab) having the chemical composition of the above is heated, and hot rolling is performed on the heated steel ingot to obtain a hot-rolled plate. Here, the heating temperature of the steel ingot when subjected to hot rolling is not specifically specified, but it is preferable to be, for example, 1050 to 1250°C. In addition, the plate thickness of the hot-rolled plate after hot rolling is not specifically specified, but considering the final plate thickness of the base material, it is preferable to be, for example, about 1.5 to 3.0 mm.

[0132] Hot Rolled Plate Annealing Process

[0133] Subsequently, hot-rolled sheet annealing is performed for the purpose of reducing iron loss in the steel sheet. For hot-rolled sheet annealing, it is desirable to use a continuous annealing furnace, which offers higher productivity and higher homogeneity of the metal structure after annealing compared to batch annealing. Furthermore, as mentioned above, if the Si content in the steel sheet is high and it is necessary to reduce the sheet thickness to reduce iron loss, it is desirable to lower the cracking temperature during hot-rolled sheet annealing. Therefore, hot-rolled sheet annealing is performed under conditions where the cracking temperature is 800 to 920°C and the cracking time is 1 second to 10 minutes. To obtain good magnetic properties, a temperature of 820°C or higher is desirable. To obtain good toughness, a temperature of 900°C or lower is desirable.

[0134] Descaling Process

[0135] After the annealing of the above hot-rolled steel plate, shot blasting is performed, followed by pickling, to remove the scale layer formed on the surface of the base material. Since a scale layer develops during the annealing of the hot-rolled plate, shot blasting is performed before pickling, thereby facilitating descaling through subsequent pickling. Here, the pickling conditions, such as the concentration of the acid used for pickling, the concentration of the accelerator used for pickling, and the temperature of the pickling solution, are not particularly limited and can be any known pickling conditions.

[0136] Cold Rolling Process

[0137] Cold rolling is performed on the steel sheet after the above descaling. In cold rolling, the base material is rolled at a reduction rate such that the final plate thickness becomes 0.10 to 0.30 mm.

[0138] <Final Annealing Process>

[0139] After the above cold rolling, finish annealing is performed. In the method for manufacturing a non-oriented electrical steel sheet according to the present embodiment, it is preferable to use a continuous annealing furnace for finish annealing. Finish annealing is performed under conditions where the cracking temperature is 900 to 1050°C and the cracking time is 1 second to 10 minutes. It is preferable to set the atmosphere to a mixed atmosphere of H2 and N2 with an H2 ratio of 1 to 100 volume% (i.e., H2+N2=100 volume%) and to set the dew point of the atmosphere to -50 to +10°C.

[0140] If the cracking temperature is less than 900°C, the crystal grain size becomes fine, which is undesirable as iron loss deteriorates; if the cracking temperature exceeds 1050°C, the strength becomes insufficient, which is undesirable as iron loss also deteriorates. In addition, if the cracking time is less than 1 second, the crystal grains cannot grow sufficiently. On the other hand, if the cracking time exceeds 10 minutes, it causes an increase in manufacturing costs.

[0141] In this embodiment, rapid heating is performed during the finishing annealing process to suppress the development of a texture that is unfavorable to magnetic properties. Therefore, during the finishing annealing process, the material is heated to a temperature of 850°C or higher such that the heating rate in the temperature range of 500°C to 850°C is 400°C / s or higher.

[0142] By setting the heating rate to 400°C / s or higher, it becomes possible to suppress the development of textures that are detrimental to magnetic properties. A heating rate of 800°C / s or higher is preferable, and 1000°C / s or higher is more preferable. Since a faster heating rate is better, there is no need to set a specific upper limit; however, considering equipment constraints, a heating rate of 2000°C / s or lower is preferable. In addition, as described above, magnetic properties can be improved by performing rapid heating to a temperature of 850°C or higher. Furthermore, in the entire heating process including the temperature range below 500°C and the cracking temperature, the average heating rate may be 1 to 2000°C / s.

[0143] Furthermore, rapid heating under the aforementioned conditions is difficult with conventional direct heating of gas combustion, radiant tubes, electric heaters, etc. Therefore, in this embodiment, it is preferable to use electric heating, induction heating, etc.

[0144] Insulating film formation process

[0145] After the above finishing annealing, an insulating film forming process is performed as needed. Here, the method of forming the insulating film is not particularly limited, and the treatment solution for forming a known insulating film as described below can be used, and the treatment solution can be applied and dried by a known method. As a known insulating film, for example, a composite insulating film that is mainly composed of inorganic materials and further includes organic materials can be cited.

[0146] A composite insulating film is an insulating film in which fine organic resin particles are dispersed, with at least one of the following as the main component: a metal salt, such as a metal chromate salt or a metal phosphate salt, or an inorganic material, such as colloidal silica, a Zr compound, or a Ti compound. In particular, from the perspective of reducing the environmental burden during manufacturing, which has been a growing demand in recent years, an insulating film using a coupling agent of a metal phosphate salt, Zr, or Ti as a starting material, or an insulating film using a carbonate or ammonium salt of a coupling agent of a metal phosphate salt, Zr, or Ti as a starting material, is preferably used.

[0147] The surface of the base material on which the insulating film is to be formed may undergo any pretreatment, such as degreasing with alkali or pickling with hydrochloric acid, sulfuric acid, phosphoric acid, etc., before applying the treatment solution. Alternatively, the treatment solution may be applied to the surface of the base material immediately after final annealing without performing these pretreatments.

[0148] The non-oriented electrical steel sheet of the present invention obtained as described above is suitable as a material for either a rotor core or a stator because it possesses excellent characteristics such as low iron loss, high magnetic flux density, and high strength.

[0149] The present invention will be explained more specifically below by way of examples, but the present invention is not limited to these examples.

[0150] Examples

[0151] A slab having the chemical composition shown in Table 1 was heated to 1150°C, then hot-rolled at a finishing temperature of 850°C and a finishing plate thickness of 2.0 mm, and coiled at 600°C to produce a hot-rolled steel sheet. The obtained hot-rolled steel sheet was annealed using a continuous annealing furnace under the conditions shown in Table 2. The steel sheet obtained in this way was descaled by shot blasting and pickling, and then cold-rolled to produce a cold-rolled steel sheet with the plate thickness shown in Table 2.

[0152] In addition, finish annealing was performed under the conditions shown in Table 2 in a mixed atmosphere of H2: 20%, N2: 80%, and a dew point of -30°C. Furthermore, induction heating was used for the temperature increase during finish annealing, and rapid heating was performed to the target temperature shown in Table 2. Additionally, heating was performed using a radiant tube for the temperature increase process from the target temperature to the cracking temperature and the cracking process. The temperature increase rate from the target temperature to the cracking temperature was approximately 5°C / s. After finish annealing, an insulating film consisting of aluminum phosphate and an acrylic-styrene copolymer resin emulsion with a particle size of 0.2 μm was applied to the steel sheet, and it was baked in the atmosphere at 350°C.

[0153]

[0154]

[0155] For each obtained test specimen, the average grain size of the base material was measured according to JIS G 0551: 2013 “Steel—Microscopic Examination Method for Grain Size.” In addition, Epstein specimens were taken from the rolling direction and width direction of each test specimen, and the iron loss W was determined by the Epstein test according to JIS C 2550-1: 2011. 10 / 400 and magnetic flux density B 50 It was evaluated. In addition, the density of the steel plate was 7.65 g / cm³ 3 Self-measurement was performed.

[0156] The concentration of {111} orientation on the polished surface, in which the base material of each test material was removed from one side surface to a depth of 1 / 4 of the plate thickness by chemical polishing, was obtained from the Orientation Distribution Functions (ODF) representing the three-dimensional texture calculated by the series expansion method based on the pole figures of the {200} plane, {110} plane, {310} plane, and {211} plane on α-Fe measured by an X-ray diffraction device.

[0157] Next, JIS No. 5 tensile test specimens were taken from each test material in accordance with JIS Z 2241: 2011, such that the longitudinal direction coincided with the rolling direction of the steel plate. Then, using the above test specimens, a tensile test was performed in accordance with JIS Z 2241: 2011, and the tensile strength was measured.

[0158] The above results are shown together in Table 2.

[0159] In tests No. 2, 3, 5, 6, 9, 12, 15, 17, 22, 25, 27, and 28 satisfying the provisions of the present invention, iron loss W 10 / 400 This is low, and magnetic flux density B 50 It was found that it has a high tensile strength of over 580 MPa.

[0160] In contrast to those, in comparative example tests No. 1, 4, 7, 8, 10, 11, 13, 14, 16, 18 to 21, 23, 24, 26, and 29, iron loss W 10 / 400 If this drops, or magnetic flux density B 50 Manufacturing became difficult as the strength decreased, tensile strength dropped, or toughness significantly deteriorated.

[0161] Specifically, in Test No. 1, because the heating rate during final annealing was lower than the specified range, the density of {111} orientations exceeded the specified range, resulting in a decrease in magnetic flux density. In Test No. 4, because the temperature reached during rapid heating during final annealing was lower than the specified range, the density of {111} orientations exceeded the specified range, resulting in a decrease in magnetic flux density.

[0162] In Test No. 7, the plate thickness was thicker than the specified range, resulting in a decrease in iron loss. In Test No. 8, the S content was higher than the specified range, leading to an increased amount of MnS precipitation and a decrease in iron loss. In Test No. 10, the total content of Sn and Sb was lower than the specified range, causing the {111} orientation density to exceed the specified range and resulting in a decrease in magnetic flux density. In Test No. 11, the total content of Sn and Sb was higher than the specified range, causing toughness to deteriorate and fracture during cold rolling, making it impossible to measure tensile strength and magnetic properties.

[0163] In Test No. 13, the magnetic flux density decreased because the Mn content was higher than the specified range. In Test No. 14, iron loss and tensile strength decreased because Si+Al+0.5×Mn was lower than the specified range. In Test No. 16, since Si+Al+0.5×Mn was higher than the specified range, toughness deteriorated and fracture occurred during cold rolling, making it impossible to measure tensile strength and magnetic properties.

[0164] In Test No. 18, the tensile strength decreased because the Si content was lower than the specified range. In Test No. 19, the toughness deteriorated because the Si content was higher than the specified range, causing fracture during cold rolling, making it impossible to measure tensile strength and magnetic properties. In Test No. 20, the average crystal grain size after finish annealing became smaller than the specified range because the Al content was lower than the specified range, resulting in reduced iron loss.

[0165] In Test No. 21, because the cracking temperature during hot-rolled sheet annealing was lower than the specified range, the density of {111} orientations exceeded the specified range, resulting in a decrease in magnetic flux density. In Test No. 23, because the cracking temperature during hot-rolled sheet annealing was higher than the specified range, toughness deteriorated and fracture occurred during cold rolling, making it impossible to measure tensile strength and magnetic properties. In Test No. 24, because the Al content was higher than the specified range, toughness deteriorated and fracture occurred during cold rolling, making it impossible to measure tensile strength and magnetic properties.

[0166] In Test No. 26, the cracking temperature during finishing annealing was lower than the specified range, resulting in an average grain size smaller than the specified range and a decrease in iron loss. In Test No. 29, the cracking temperature during finishing annealing was higher than the specified range, resulting in an average grain size larger than the specified range and a decrease in tensile strength. Industrial applicability

[0167] As described above, according to the present invention, a non-oriented electrical steel sheet having excellent magnetic properties and high strength can be stably obtained at a low cost.

Claims

Claim 1 The chemical composition of the base material, in mass%, is C: 0.0040% or less, Si: greater than 3.50% and less than or equal to 4.50%, Mn: greater than 0% and less than 0.60%, Al: 0.30 to 0.90%, P: 0.030% or less, S: 0.0018% or less, N: 0.0040% or less, Ti: less than 0.0040%, Nb: greater than 0% and less than 0.0050%, Zr: greater than 0% and less than 0.0050%, V: greater than 0% and less than 0.0050%, Cu: less than 0.200%, Ni: less than 0.500%, the sum of one or two of Sn and Sb: 0.005 to 0.060%, and the remainder: Fe and impurities, satisfying the following equation (i), and the average determination of the base material A non-oriented electrical steel sheet having a particle size greater than 40㎛ and less than or equal to 140㎛, a density of {111} orientation at a position 1 / 4 of the plate thickness from the surface of the base material of the above material of 4.0 or less, and a plate thickness of the above material of 0.10 to 0.30mm. 4.2≤Si+Al+0.5×Mn≤4.9 … (i) wherein the element symbols in the above formula represent the content (mass%) of each element. Claim 2 In claim 1, a non-oriented electrical steel sheet having a tensile strength of 580 MPa or more. Claim 3 A non-oriented electrical steel sheet having an insulating film on the surface of the base material in claim 1 or 2. Claim 4 A method for manufacturing a non-oriented electrical steel sheet as described in claim 1 or 2, wherein, in mass%, C: 0.0040% or less, Si: greater than 3.50% and less than or equal to 4.50%, Mn: greater than 0% and less than 0.60%, Al: 0.30 to 0.90%, P: 0.030% or less, S: 0.0018% or less, N: 0.0040% or less, Ti: less than 0.0040%, Nb: greater than 0% and less than 0.0050%, Zr: greater than 0% and less than 0.0050%, V: greater than 0% and less than 0.0050%, Cu: less than 0.200%, Ni: less than 0.500%, total of one or two of Sn and Sb: 0.005 to 0.060%, remainder: Fe and impurities, and the following (i) A method for manufacturing a non-oriented electrical steel sheet, wherein for a steel ingot having a chemical composition satisfying the formula, a hot rolling process, a hot-rolled sheet annealing process in which the cracking temperature is 800 to 920°C and the cracking time is 1 second to 10 minutes, a descaling process in which pickling is performed after shot blasting, a cold rolling process in which the sheet thickness is reduced to 0.10 to 0.30 mm, and a finishing annealing process in which the cracking temperature is 900 to 1050°C and the cracking time is 1 second to 10 minutes are performed in sequence after heating to a temperature of 850°C or higher such that the heating rate in the temperature range of 500 to 850°C is 400 to 2000°C / s. 4.2≤Si+Al+0.5×Mn≤4.9 … (i) wherein the element symbols in the above formula represent the content (mass%) of each element.

Citation Information

Patent Citations

  • Nonoriented electromagnetic steel sheet and manufacturing method therefor

    JP2018178197A

  • Non-oriented electrical steel sheet and manufacturing method therefor

    WO2021125856A2

  • Non-oriented electromagnetic steel sheet and method for manufacturing same

    WO2021210672A1